(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
The creative process in urban planning is based on careful preservation of past examples, cultural and architectural monuments, but at the same time rejects blind imitation, because the developing society constantly changes its material, aesthetic forms and ideals. People’s self-awareness and cultural change, the development of construction techniques, the appearance of new building materials, which led to a high level of development of architecture. Therefore, all the design and construction process carried out in the urban development is necessarily carried out on the basis of conditions and factors representing national traditions. This article examines the principles of development of the tasks set in urban planning based on national historical traditions.